Comprehensive analysis of current research trends in energy storage technologies - Surender Reddy Salkuti; Sravanthi Pagidipala; Seong-Cheol Kim (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
This paper addresses the comprehensive analysis of various energy storage technologies, i.e., electrochemical and non-electrochemical storage systems by considering their storage methods, environmental impact, operations, costs, and their importance and applications. These storage technologies will help to reduce the energy shortage. There has been a significant deployment of storage systems in power grids throughout the world. The characteristics of storage systems such as the ability to act both as generation and load, fast response time, and high ramp rate. Make them promising options for the system operators to reduce the peak demand, and facilitate renewable energy integration. Various new trends in energy depict the ways this generated energy could be stored and harnessed. With the recent integration of renewable energy, it is important to store the energy and it is combined to help the green energy demand. The integration of renewable energy into the power grid has increased reliability, efficiency, and stability. Adding the energy component will further enhance the capabilities of the grid. This paper also recommends an optimal storage technique from various available storage technologies.